Enhancement of gene expression and melanin production of human tyrosinase gene loaded in elastic cationic niosomes - Khositsuntiwong N. (2014)
Objectives Disturbance in the synthesis of tyrosinase might be one of the major causes of vitiligo. The enhancement of tyrosinase gene expression and melanin production by loading the plasmid in elastic cationic niosomes was investigated in tyrosinase gene knocked out human melanoma (M5) cells and in tyrosine-producing mouse melanoma (B 16F 10) cells. Methods Niosomes composed of Tween 61/cholesterol/dimethyl dioctadecyl ammonium bromide at 1: 1: 0.5 molar ratio were prepared by the freeze-dried empty liposomes method. The thin lipid film was redissolved in distilled water or 25% ethanol to obtain the non-elastic or elastic cationic niosomes, respectively. Key findings The maximum loading of the plasmid in non-elastic and elastic niosomes was 130 and 100 μg per 16 mg of the niosomal contents, respectively. The plasmid-loaded elastic cationic niosomes exhibited high specific tyrosinase activity of 1.66 and 1.50 fold in M5 cells and 6.81 and 4.37 fold in B 16F 10 cells compared with the free plasmid and the plasmid-loaded non-elastic cationic niosomes, respectively. Conclusions This study has demonstrated not only the enhancement of the expression of human tyrosinase gene by loading in elastic cationic niosomes, but also the potential application of this gene delivery system for the further development of vitiligo gene therapy. © 2012 The Authors. JPP © 2012 Royal Pharmaceutical Society.